45‐4: Approach for Attaining Short Exciton Lifetime in Thermally Activated Delayed Fluorescence Emitters. Issue 1 (May 2017) - Lampande, Raju; Kim, Gyeong Heon; Im, Joon Beom; Kim, Kwang Jong; Lee, Ju Young; Kwon, Jang Hyuk
Abstract : We report an approach to achieve short delayed fluorescence exciton lifetime in efficient green and blue thermally activated delayed fluorescence (TADF) emitters. The synthesized TADF emitters show small singlet‐triplet energy splitting, high photoluminescence quantum yields, and proper charge transfer characteristics, resulting in short delayed fluorescence exciton lifetime. The fabricated organic light emitting diodes with green and deep blue TADF emitters display maximum external quantum efficiency of 31.4% and 22.5%, respectively, and significantly low efficiency roll‐off characteristics.